Proposal of the pipe diagnosis method using in-plane bending vibration of cylindrical shell - Soichiro TAKATA; Hirofumi INOUE; Shigeki SHINODA (Nihon Kikai Gakkai ronbunshu, 2018)
In this paper, deterioration diagnosis for distribution main pipe was studied using the uniform cylindrical shell approximation and in-plane bending mode. The in-plane bending mode is expected to have high accuracy in detection of deterioration, because the eigen frecuency of the mode is proportional to pipe thickness. First, using the finite element method, the characteristics of in-plane bending mode are investigated. It is confirmed that in-plane bending mode has little small dependence on the pipe length and the boundary conditions at the pipe ends, it appears in the audio frequency bands, and it has linear dependence on the pipe thickness. In addition, formula with two dimensional ring approximation is derived. Moreover, the average thickness and the uniform-cylindrical shell approximation are introduced for deal with the deteriorated pipe. Using the thinning pipe thickness of previous study, validity of the average thickness and the uniform-cylindrical shell approximation were confirmed. On the other hand, actual pipeline has the sub-structure, for example, valve, hydrant, and so on. In order to deal with the coupled vibration between the cylindrical shell and the sub-structure, eigenvalue analysis are conducted using the Semi-Analytical Receptance Method (SARM). The experimental consideration were conducted in case of that the sub-structure non-attached case. The in-plane bending mode is observed experimentally on the actual pipe system and its resonant frequency shows good match with the theoretical values.